Hunting Traps around the Oasis of ʿEn Gedi - Hadas, Gideon (Israel exploration journal, 2011)
While surveying the ʿEn Gedi Oasis and its environs, several ancient hunting traps were found; some are predator traps and one is a 'desert kite'. Predator traps, found in the Sinai Peninsula, the Negev and now in the Judaean Desert, are generally referred to as 'leopard traps'. The leopard is the top predator in these regions that preyed on domestic flocks as well as on wild fauna. The traps found around ʿEn Gedi were built to protect the oasis from predator infiltration. The 'desert kite' is a hunting installation probably used to catch gazelles.